Analysis of the Influence of Dynamic Load on the Work Parameters of a Powered Roof Support’s Hydraulic Leg - Szurgacz, Dawid; Brodny, Jarosław (Sustainability, 2019)
One of the basic tasks of powered roof support is to protect the longwall excavation against deformation of the rock mass during the underground exploitation of hard coal. The behavior of the rock mass during mining is difficult to predict. Therefore, the loads acting on the support are diverse in terms of nature, direction and force. The dynamic load resulting from rock bursts, relaxation and tremors may lead to particularly dangerous consequences involving the functionality of the workings and the safety of the crew. The powered roof support will function properly only if the elements dynamically loaded are under control at the moment of impact. The article presents the results of tests of the basic powered roof support’s element − a hydraulic leg impacted by dynamic load. The source of the load was a free falling impact mass dropped from a certain height. The tests covered the actual hydraulic leg with all hydraulic equipment used in the powered roof support. During the tests, the original measurement-recording system developed by the authors was used, in which, among others, a high-speed dynamic camera was used to record movements of the leg’s elements. The original research methodology developed together with the measurement system enabled the registration of many parameters of the leg’s work under dynamic load. In particular, this applies to time series of pressure in the leg and the value of its withdrawal depending on the energy of the impact. The individual phases of the leg’s work were also registered, including the opening and closing of the safety valve protecting the leg against overloading. The obtained results broaden knowledge in the field of hydraulic legs used in the mining support under dynamic load. At the same time, they are a valuable source of information for mine maintenance services and should be applied to the design process, selection and operation of a powered roof support in dynamic conditions. The subject of the article fits in with the philosophy of sustainable development, especially in the field of full use of options of the support and ensuring safe and environmentally friendly mining processes.